Praziquantel, mefloquine-praziquantel, and mefloquine-artesunate-praziquantel against Schistosoma haematobium: a randomized, exploratory, open-label trial. - Jennifer Keiser; Kigbafori D Silué; Lukas K Adiossan; Nicaise A N'Guessan; N'Chou Monsan; Jürg Utzinger; Eliézer K N'Goran (PLoS Neglected Tropical Diseases, 2014)
Treatment and morbidity control of schistosomiasis relies on a single drug, praziquantel. Hence, there is a pressing need to develop additional therapeutics against schistosomiasis. The antimalarial drug mefloquine shows antischistosomal activity in animal models and clinical trials, which calls for further investigations.We comparatively assessed the efficacy and tolerability of the following treatments against Schistosoma haematobium in school-aged children in Côte d'Ivoire: (i) praziquantel (40 mg/kg; standard treatment); (ii) mefloquine (25 mg/kg) combined with praziquantel (40 mg/kg); and (iii) mefloquine-artesunate (3× (100 mg artesunate +250 mg mefloquine)) combined with praziquantel (40 mg/kg) (treatments administered on subsequent days). Two urine samples were collected before, and on days 21-22 and 78-79 after the first dosing.Sixty-one children were present on all examination time points and had complete datasets. No difference in efficacy was observed between the three treatment groups on either follow-up. On the 21-22 day posttreatment follow-up, based on available case analysis, cure rates of 33% (95% confidence interval (CI) 11-55%), 29% (95% CI 8-50%), and 26% (95% CI 5-48%) were observed for praziquantel, mefloquine-artesunate-praziquantel, and mefloquine-praziquantel, respectively. The corresponding egg reduction rates were 94% and above. On the second follow-up, observed cure rates ranged from 19% (praziquantel) to 33% (mefloquine-artesunate-praziquantel), and egg reduction rates were above 90%. Praziquantel monotherapy was the best tolerated treatment. In the mefloquine-artesunate-praziquantel group, adverse events were reported by 91% of the participants, and in the mefloquine-praziquantel group, 95% experienced adverse events. With the exception of abdominal pain at moderate severity, adverse events were mild.The addition of mefloquine or mefloquine-artesunate does not increase the efficacy of praziquantel against chronic S. haematobium infection. Additional studies are necessary to ...